2021
DOI: 10.21705/mcbs.v5i2.191
|View full text |Cite
|
Sign up to set email alerts
|

Low Total Lymphocyte Count as the Risk of Hospital Acquired Malnutrition in Children

Abstract: Background: Hospital Acquired Malnutrition (HAM) is characterized by inadequate nutritional therapy and the risk of developing malnutrition during the hospital stay. In clinical practice, there are many measurements to determine nutritional status. Total lymphocyte count (TLC) is associated with impaired function of immune system in malnutrition. The purpose of this study was to evaluate the prognostic value of TLC to the occurrence of HAM in pediatric patients.Materials and Methods: This an observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The TLC can be used to detect malnutrition. Children with a low TLC on admission to hospital had a 3.9-fold risk of hospital-acquired malnutrition [ 18 ]. An ONS is useful to improve immune function, inflammatory response and treatment efficacy in cancer patients [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLC can be used to detect malnutrition. Children with a low TLC on admission to hospital had a 3.9-fold risk of hospital-acquired malnutrition [ 18 ]. An ONS is useful to improve immune function, inflammatory response and treatment efficacy in cancer patients [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition accompanied by infection also decreases B lymphocyte subsets (such as CD20 + ), which is caused by malnutrition-related immunodeficiency [ 17 ]. Total lymphocyte count (TLC) has been used as one prognostic variable to detect malnutrition because its decrease can be correlated with malnutrition [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Authors relay that other factors may influence the development of prosocial behavior including nutritional intake and the history of hospitalization as well as chronic infection such as tuberculosis. (36,37) This study use the non-prospective design and not all factors that may influence prosocial behavior were observed, therefore future research supposed to be delivered with better design and control of other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Using a cut-off value of 4,000 cells/mm 3 , children between the ages of 6 and 12 months were found to have a 61.8% hospital malnutrition incidence rate and a 32.3% rate of normal TLC, as well as a 3.9 times higher risk of hospital malnutrition for those with low TLC, with a 95% confidence interval between 1.5 and 7.1. These data suggested that low TLC levels can be used to predict the development of hospital malnutrition (Ekaputri et al 2021).…”
Section: The Strongkids and Biochemical Parametersmentioning
confidence: 92%